2016
DOI: 10.5152/tao.2016.1501
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Analysis of Surgically Managed Maxillofacial Fractures in Kayseri Training and Research Hospital

Abstract: Objective: To retrospectively evaluate the clinical and surgical data of patients with maxillofacial fracture (MFF) who were surgically treated at the Department of ENT and Head Neck Surgery in the Kayseri Training and Research Hospital and to compare and discuss the results with relevant literature, including that from Turkey. Results: A total of 35 patients were surgically treated because of MFF between January 2013 and March 2015. Of the 35 patients, 28 (80%) were male, whereas seven (20%) were female. Traf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…When maxillofacial fractures were assessed, there was an isolated maxillary fracture in 14 patients and concurrent mandibular and maxillary fractures in 17 patients in our study. In a study of 35 patients from Turkey, Yasar et al 13 reported that there was a mandibular fracture in 28 patients and a unifocal fracture in 13 patients; parasymphysis was the most commonly involved region, followed by angulus, ramus, and condyle fracture. In our study, ramus fractures and multifocal mandibular fractures were more common.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When maxillofacial fractures were assessed, there was an isolated maxillary fracture in 14 patients and concurrent mandibular and maxillary fractures in 17 patients in our study. In a study of 35 patients from Turkey, Yasar et al 13 reported that there was a mandibular fracture in 28 patients and a unifocal fracture in 13 patients; parasymphysis was the most commonly involved region, followed by angulus, ramus, and condyle fracture. In our study, ramus fractures and multifocal mandibular fractures were more common.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, ramus fractures and multifocal mandibular fractures were more common. In the study by Yasar et al, 13 the etiology underlying maxillofacial fractures included traffic accidents, assault, and less commonly, sports injuries. The type of fracture also differs since mechanisms underlying maxillary and mandibular fracture are variable.…”
Section: Discussionmentioning
confidence: 99%
“…The epidemiologic information on maxillofacial injuries has changed with the onset of motor vehicle seat belt and airbag laws, reduced speed limits, and increasing urban violence. RTA is the most common cause of maxillofacial fractures in most papers published in Turkey 1,6,8,9,11,15 . In a study from the capital city of Turkey between 1991 and 2000, Şimşek et al 1 reported that the most common cause of mandibular fracture was RTA (36.2%).…”
Section: Discussionmentioning
confidence: 99%
“…Also the patterns of maxillofacial fractures differ among economic, social and cultural variance of the examined population and geographic regions [1][2][3][4][5][6][7][8] . Maxillofacial trauma can be managed by different specialities with different treatment approaches based mostly on availability and experience of institutions 6,9,10 . Mandibular bone is among the most commonly fractured bones during maxillofacial trauma, and consists the majority of traumatic injuries treated by the oral and maxillofacial surgeons 1,2,6 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation